Mapping and Analysis of Bangka’s Local Tax Potential - Altin, Darus; Wahyudin, Nanang; Elma, Elma; Ridwan, Muhammad Qomaruddin (Goodwood Publishing, 2026)
Purpose: The aim of this research is to compile data on the potential tax of hotels, restaurants, and entertainment in Bangka Regency in 2023. Research Methodology: We used in this study are primary and secondary data. The researcher used stratified random sampling for fifty-one Local Taxpayers in Bangka Regency. Data analysis employed a micro approach to obtain target projections and potential local tax revenue projections in Bangka Regency, specifically for Certain Goods and Services Tax (Restaurant Tax, Hotel Tax, and Entertainment Tax). Results: Research findings indicate that it is possible to improve the realization of Restaurant Tax revenue in the future. The biggest potential for Hotel from 4-star hotels.About 11% of Entertainment Tax potential has been realized, so it is very likely to improve the realization of Entertainment Tax revenue in the future. Conclusions: Hotel and restaurant taxes fall into the developing category, while entertainment tax falls into the backward category. The growth projections for hotel and restaurant taxes can be further improved in the future. Innovative programs and more attention to local taxes in the backward category are efforts to enhance regional tax revenue. Limitations: This research is limited to examining three studies of local tax objects in Bangka Regency. Contribution: For future researchers, it is recommended to further examine the aspects of compliance of Local Taxpayers and to delve deeper into other Local Tax objects not included in this study.